Pediatric cardiologyTranscatheter closure of ventricular septal defects with nitinol wire occluders of type patent ductus arteriosus - Wierzyk, Arkadiusz; Szkutnik, Małgorzata; Fiszer, Roland; Banaszak, Paweł; Pawlak, Szymon; Białkowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Ventricular septal defects closure (VSD) depending on the anatomy and clinical setting can be performed surgically or by a hybrid and transcatheter approach. Two cases of children with VSD will be presented. Patients’ defects were closed with various types of occluders made of nitinol wire mesh occluder, patent ductus arteriosus (PDA) type. The first case was a 2.5-year-old boy after cardiosurgical correction of tetralogy of Fallot (TOF). After the procedure, a significant haemodynamic residual VSD was observed, which was not successfully closed during the subsequent reoperation. Despite pharmacological treatment, symptoms of heart failure were observed in this patient. In echocardiographic images the residual VSD was presented as a tunnel-like dissection of the ventricular septum (length 6 mm and diameter 3.4 mm). The defect was closed via arterial access with an Amplatzer Duct Occluder II (ADO II). The procedure was successfully performed without any medical complications. In this child, a significant shunt reduction and a noticeable improvement in the patient’s clinical status and diminished symptoms of heart failure were noticed. The second patient was a 4-year-old girl suffering from a multi-perforated perimembranous VSD accompanied by a ventricular septal defect with aneurysm. The defect was closed by a venous approach with a PDA Cardio-O-Fix occluder (very similar to ADO I). No short-term or long-term complications were visible during or after the procedure. Only a mild residual shunt through the VSD was observed 6 months afterwards. Transcatheter VSD closure with a proper morphology, with occluders of type Amplatzer Duct Occluder ADO I or ADO II, constitutes a safe and effective therapeutic alternative.